2016
DOI: 10.1186/s13054-015-1157-5
|View full text |Cite
|
Sign up to set email alerts
|

The leukocyte-stiffening property of plasma in early acute respiratory distress syndrome (ARDS) revealed by a microfluidic single-cell study: the role of cytokines and protection with antibodies

Abstract: BackgroundLeukocyte-mediated pulmonary inflammation is a key pathophysiological mechanism involved in acute respiratory distress syndrome (ARDS). Massive sequestration of leukocytes in the pulmonary microvasculature is a major triggering event of the syndrome. We therefore investigated the potential role of leukocyte stiffness and adhesiveness in the sequestration of leukocytes in microvessels. MethodsThis study was based on in vitro microfluidic assays using patient sera. Cell stiffness was assessed by measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 48 publications
(68 reference statements)
2
24
0
Order By: Relevance
“…Conversely, the double constriction device allows an accurate comparison of cell properties in a wide range of stiffness, which has allowed us to investigate pathologies involving the plugging of lung microvasculature by stiffened leukocytes. 56 In the present work, we demonstrate how this device can also be used to infer quantitative rheological analysis on single cells.…”
Section: Resultsmentioning
confidence: 87%
“…Conversely, the double constriction device allows an accurate comparison of cell properties in a wide range of stiffness, which has allowed us to investigate pathologies involving the plugging of lung microvasculature by stiffened leukocytes. 56 In the present work, we demonstrate how this device can also be used to infer quantitative rheological analysis on single cells.…”
Section: Resultsmentioning
confidence: 87%
“…Not only in animal model, but also human septic cases showed up-regulation of integrin α4β1on neutrophils [9,10] . On the other hand, increased expression of integrin α4β1on neutrophils was not recognized in early stage of acute respiratory distress syndrome (ARDS) cases in another paper [11] . They discussed that increased expression level of adhesion molecule might be delay, several hours later.…”
Section: Integrin α4β1mentioning
confidence: 95%
“…Neutrophil size increases in trauma patients prior to organ dysfunction [Hesselink et al., ] and neutrophil deformability decreases in patients with chronic renal failure [Skoutelis et al., ]. Treatment of neutrophils and monocytes with serum from patients with acute respiratory distress syndrome induces rapid cellular stiffening [Preira et al., ]. In line with this observation, RT‐DC showed that patients with acute lung injury (ALI) and patients hospitalised with viral respiratory tract infections (RTI) have larger and more deformable neutrophils in their blood than healthy volunteers [Toepfner et al., ].…”
Section: The Mechanical Signature Of Myeloid Cells Associated With DImentioning
confidence: 99%